2018
DOI: 10.1111/afe.12290
|View full text |Cite
|
Sign up to set email alerts
|

Spillover of Drosophila suzukii between noncrop and crop areas: implications for pest management

Abstract: Semi‐natural areas may promote Drosophila suzukii population dynamics by providing alternative host resources, overwintering habitats and refuge areas during cold, warm or dry periods, or when crops are sprayed with insecticides. In the present study, we investigated the spillover of D. suzukii between noncrop and crop areas using sweet cherry as a model crop. We sampled the pest at different heights and at different distances from the forest, from the the winter dormancy stage to the post‐harvest period. Dros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…Tonina et al . () also found that vertical and horizontal movement of D. suzukii is dependent on host availability in sweet cherry. Additionally, it is possible that the presence of our yeast‐sugar traps may alter their behaviour or movement patterns.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Tonina et al . () also found that vertical and horizontal movement of D. suzukii is dependent on host availability in sweet cherry. Additionally, it is possible that the presence of our yeast‐sugar traps may alter their behaviour or movement patterns.…”
Section: Discussionmentioning
confidence: 80%
“…). Although there was no statistical difference of infestation between the crop adjacent to a honeysuckle bush and the crop adjacent to a nonhost, infestation was consistently higher near the wild host and may represent a spillover effect (Rand et al ., ; Tonina et al ., ). In the later part of the season, when fly populations were very high at these unmanaged sites, infestation was found throughout the blueberry field regardless of location.…”
Section: Discussionmentioning
confidence: 97%
“…Host phenology drives infestation timing, with flies preferring soft ripe fruit over firm unripe fruit (Burrack et al 2013. The presence of non-crop habitat, which can serve as a source of infesting populations or provide D. suzukii with refuge from management treatments within crop fields, might also affect D. suzukii activity patterns related to host use (Klick et al 2016, Tonina et al 2018. Despite these and other recent advances, more information regarding the behavior of D. suzukii in agroecosystems is needed in order to develop management strategies that go beyond preventative insecticide use.…”
mentioning
confidence: 99%
“…There are currently far‐reaching debates on the future of pesticide use, especially in Europe . Furthermore, the diversity of growers' strategies to combat D. suzukii is particularly relevant for European fruit and wine production, which is characterized by small‐scale production systems with successively maturing host crops grown close together and widespread semi‐natural vegetation structures, which facilitate the spill‐over of D. suzukii …”
Section: Introductionmentioning
confidence: 86%
“…33 Furthermore, the diversity of growers' strategies to combat D. suzukii is particularly relevant for European fruit and wine production, which is characterized by small-scale production systems with successively maturing host crops grown close together and widespread semi-natural vegetation structures, which facilitate the spill-over of D. suzukii. 20,[34][35][36][37][38][39] This paper aims to fill these research gaps by evaluating the real-world use of existing control practices implemented by growers in response to D. suzukii. We define control methods as individual measures and management strategies as a set of control measures adopted on a given vineyard.…”
Section: Introductionmentioning
confidence: 99%